Impact shock frequency components and attenuation in rearfoot and forefoot running - Allison H. Gruber; Katherine A. Boyer; Timothy R. Derrick; Joseph Hamill (Elsevier, 2014)
Background: The forefoot running footfall pattern has been suggested to reduce the risk of developing running related overuse injuries due to a reduction of impact related variables compared with the rearfoot running footfall pattern. However, only time-domain impact variables have been compared between footfall patterns. The frequency content of the impact shock and the degree to which it is attenuated may be of greater importance for injury risk and prevention than time-domain variables. Therefore, the purpose of this study was to determine the differences in head and tibial acceleration signal power and shock attenuation between rearfoot and forefoot running. Methods: Nineteen habitual rearfoot runners and 19 habitual forefoot runners ran on a treadmill at 3.5 m/s using their preferred footfall patterns while tibial and head acceleration data were collected. The magnitude of the first and second head acceleration peaks, and peak positive tibial acceleration were calculated. The power spectral density of each signal was calculated to transform the head and tibial accelerations in the frequency domain. Shock attenuation was calculated by a transfer function of the head signal relative to the tibia. Results: Peak positive tibial acceleration and signal power in the lower and higher ranges were significantly greater during rearfoot than forefoot running (p < 0.05). The first and second head acceleration peaks and head signal power were not statistically different between patterns (p > 0.05). Rearfoot running resulted in significantly greater shock attenuation for the lower and higher frequency ranges as a result of greater tibial acceleration (p < 0.05). Conclusion: The difference in impact shock frequency content between footfall patterns suggests that the primary mechanisms for attenuation may differ. The relationship between shock attenuation mechanisms and injury is not clear but given the differences in impact frequency content, neither footfall pattern may be more beneficial for injury, rather the type of injury sustained may vary with footfall pattern preference.